PROSES PRODUKSI PIE UBI UNGU - Nadila Dwi Prasetyo Wati; Bara Yudhistira (Universitas Sebelas Maret, 2018)
Purple sweet potato pie is a processed food made from the main ingredients of wheat flour and purple yams, and some other additives are margarine, refined sugar, milk and eggs. The process of making purple sweet potato pie includes stages of preparation of raw materials, weighing, mixing, printing, baking, cooling, and packaging. Organoleptic test of purple sweet potato pie showed panelist preferences was formulation of 60% wheat flour and 40% purple sweet potato. The content of antioxidant purple sweet potato pie was 83% and shelf life until 5 days. Economic analysis of purple sweet potato pie produced 2000 cardboard (1 month), with each cardboard containing 5 pcs. The price of purple sweet potato pie is Rp 8.000,00. The net profit of sales is Rp 8,264,953,00. Purple sweet potato pie business has reached the break even point (BEP) at the production level of 1,483 boxes. POT value or payback within 4.5 months. Net B / C value of purple sweet potato pie production is 1.16%. The NPV value is 61,027,031. IRR value of 31%, so that the business of purple sweet potato pie is feasible to run.